Effect of health campaigns through social media on changes in diabetes mellitus prevention behavior in young adults - Mery Kana; Fitri Anita (Jurnal Edukasi Ilmiah Kesehatan, 2026)
Introduction: Diabetes mellitus (DM) is an increasingly prevalent non-communicable disease among young adults, driven by unhealthy lifestyles, physical inactivity, and poor dietary habits. Social media has emerged as a widely accessible platform for health promotion, offering opportunities to disseminate preventive health information and encourage healthy behavior. This study aimed to examine the effect of health campaigns delivered via social media on diabetes prevention behaviour among young adults. Research Methodology: An analytical cross-sectional study was conducted in Makassar, Indonesia, between January and March 2026. A total of 176 young adults aged 18–35 years were recruited using stratified random sampling. Data were collected via a validated online questionnaire assessing exposure to social media health campaigns and diabetes prevention behaviours. Descriptive statistics, Pearson correlation analysis, and multiple linear regression were performed using SPSS version 29.0, with a significance level of p < 0.05. Results: The mean age of participants was 24.8 ± 4.3 years, and 58.0% were female. Exposure to social media health campaigns was positively correlated with diabetes prevention behavior (r = 0.542, p < 0.001). Multivariable linear regression showed that social media campaign exposure was the strongest predictor of diabetes prevention behavior (β = 0.468, 95% CI: 0.321–0.615, p < 0.001), followed by education level (β = 0.183, p = 0.006), daily social media use (β = 0.142, p = 0.024), and family history of diabetes (β = 0.116, p = 0.038). The final model explained 41.8% of the variance in preventive behavior (Adjusted R² = 0.418). Conclusion: Social media health campaigns are significantly associated with improved diabetes-prevention behaviours among young adults. Integrating evidence-based digital health communication into diabetes prevention programs may strengthen public health efforts to reduce future disease burden and promote healthier lifestyles among younger populations